Contending Theories of Wage Determination: An Intersectoral Analysis of Real Wage Growth in the U.S. Economy - James Sheffield (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2013)
In recent years, social movements and popular media have drawn attention to the issue of income inequality in the United States. This growing inequality in the distribution of income is often seen as a function of stagnating wage growth in the U.S. economy. There appears to be a fairly broad consensus among commentators that wage growth for many workers in the U.S. has stagnated in recent decades, though the precise causes and implications of this trend are a matter of considerable dispute. Some see it as a function of stagnant productivity growth, while others attribute it to the declining strength of the labor movement. This paper uses multiple regression analyses in an attempt to provide an empirical means to judge the theoretical salience of these contending viewpoints. The results of this study indicate that while wage growth has in fact maintained a positive correlation with productivity, this correlation is much weaker than expected, particularly for manufacturing industries. Furthermore, while labor union strength appears to be an insignificant factor in the determination of wages for manufacturing industries, it retains a strong statistical significance in service sector wages. I argue that this finding reflects a historical shift in the composition of U.S. industry. The data gathered in this study supports the view that labor union density plays a role in the strength of wage-productivity elasticity, which raises important questions of how best to conceptualize wage growth and aggregate income distribution from the standpoint of economic theory.
Keywords: Wages; Labor; Productivity